(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
Organizational culture holds significant influence in shaping the success of strategic management initiatives within higher education institutions (HEIs). Organizational culture shapes prevailing attitudes, behaviors, and collective values, which can either enhance or obstruct the realization of strategic objectives. When the culture is in harmony with the HEI’s strategy and organizational values, it ensures that all members, from top-tier leadership to operational teams, are aligned in their vision and actions, leading to a more streamlined and efficient execution of strategic plans. Conversely, a culture that is not aligned with an HEI’s strategy can introduce challenges, such as resistance to changes and operational inefficiencies. Furthermore, an effective organizational culture can foster essential qualities like innovation, responsiveness, and adaptability, which are crucial in today’s dynamic and competitive academic environment. As such, for successful strategic management, it becomes imperative for HEIs to understand and align their organizational culture appropriately with their strategic direction. This article analyzes the relationship between strategy and organizational culture as two fundamental management concepts of any HEI. The article not only analyzes the interdependence and influence between strategy and organizational culture, but also covers the nature and mechanism of the influence of organizational culture on strategy formation and implementation. In this article, the relationship between organizational culture and strategy is presented from the point of view of the analysis of various authors.